Refinamento moral nos ensaios de David Hume, 1741-1742 - Andreh Sabino Ribeiro (2019)
This research aims to offer an interpretation on David Hume's Essays, from 1741 and 1742, since the common background of moral philosophy among his contemporaries and in connection with his previous work, A Treatise of Human Nature [1739-1740]. It is argued that those Essays intend to motivate readers to be virtuous, fulfilling a usual requirement at that time, however, from an alternative theoretical foundation. The first chapter sustains that Hume is committed to a practical morality since a commercial reflection, in contrast to that reflection of the cultural and conversational models. The second chapter investigates the principles that underlie the implementation of Hume's motivational project. The third and last chapter suggests a reading of those Essays in the light of the discussion of chapters 1 and 2. The type of reflection expected of those texts consists in a "distant view", or a consideration independent from self and immediate interests, on relevant subjects of daily life. By combining informative matter with a pleasant style, Hume delivers readers general opinions that can be applied and transformed by each one according to their circumstances.